Identification and field attraction of the female sex pheromone of a kiwifruit pest, Nokona feralis (Lepidoptera: Sesiidae). Issue 9 (2nd September 2018) - Naka, Hideshi; Kubota, Seiichi; Kuchiki, Fumitaka; Shibasaki, Hiroshi; Yamamoto, Masanobu; Soejima, Yasuyoshi; Arita, Yutaka; Ando, Tetsu
ABSTRACT: Female sex pheromone of a clearwing moth Nokona feralis (Leech) (Lepidoptera: Sesiidae), a pest of kiwifruit, was identified to be a 7:3 mixture of (3 E, 13 Z )-3, 13-octadecadienyl acetate (E3, Z13-18:OAc) and (3 E, 13 Z )-3, 13-octadecadien-1-ol (E3, Z13-18:OH) by GC-EAD and GC/MS analyses. Males were attracted to wide-range mixtures of E3, Z13-18:OAc and E3, Z13-18:OH, and a 7:3 mixture of those two compounds strongly attracted the males in the field.